Palace of Justice (POJ) Putrajaya / Amy Ezrina Che Man ... [et al.] - Che Man, Amy Ezrina; Misnan, Farina Fatin; Amran, Ahmad Zulfiqar; Rafizi, Faiz Fitri; Naziron, Haziq Izzuddin (2015)
Building maintenance is part of the life building cycle. In developing country like Malaysia, it is challenging task to all the maintenance company to ensure the building is safe and comfort. For Palace of Justice, PENSERA SDN.BHD is a company that maintains this building. All matters relating to the maintenance of the building will be made by PENSERA and their contract period is 4 years. The special at this building is, the materials used in the building is a show of luxury and uniqueness of its own as the wrought iron staircase, chandeliers, granite use almost 60% in this court. The building designs with five domes at the top building, door and tiles floor makes it of Islamic Buildings. When the building a famous, it should be taken care of in terms of defect in the building. The owner of building must be sure the building is good from defect . This buildings categories as a private and confidential ( P&C) from any rental in the building. At the financial management, the cost of the provision for payment in buildings provided by the government. Payment of bills should be reduced to save costs for the buildings. What we can conclude is all the information we can already achieve desired as much as its goal the building is P & C.